DemTect effective in screening for mild cognitive impairment and mild dementia. - Troyer AK (Evidence-based Mental Health, 2004)
Does the DemTect reliably detect mild dementia and mild cognitive impairment in older adults?METHODS:Design: Prospective cohort study.Setting: Three centres in the UK; timeframe not stated.People: 121 people aged 45-92 years with possible mild to moderate Alzheimer's disease (NINCDS-ARDRA criteria; Clinical Dementia Rating scale (CDR) 1 or 2). 97 people aged 4592 years with mild cognitive impairment (Peterson criteria; CDR 0.5). 145 people aged 45-89 years with no cognitive impairment (CDR 0). Control group was divided into <60 years and >/=60 years. Alzheimer's disease group was divided into Mini-Mental State Examination (MMSE) >/=21 and MMSE <21.Test: The DemTect includes five short, easy to administer tasks that are sensitive for diagnosing dementia (word list; delayed recall of word list; number transcoding; semantic word fluency task; digit span reverse).Diagnostic standard: Full clinical assessment plus CDR to assess dementia and Peterson criteria to assess mild cognitive impairment.Outcomes: Sensitivity and specificity of DemTect and MMSE inClassifying people with mild to moderate Alzheimer's disease and mild cognitive impairment compared with full clinical assessment.MAIN RESULTS:The transformed total DemTcct score is independent of age and education and performed well when compared with MMSE. At a DemTect cut off score of 13, overall classification rate, sensitivity and specificity were high (see table 1; score of 13-18 represents appropriate cognitive power for age). Additional cut off scores were useful for predicting mild cognitive impairment and dementia (mild cognitive impairment; 9-12 points; dementia: 0-8 points; total classification rate: 85.4%).CONCLUSIONS:The DemTect is a useful scale for identifying mild cognitive impairment and early dementia in older adults. It is easy to administer and accepted well by participants.